New technologies in virtual higher education: The deepfake and the face-to-face translation technologies - Miquel-Vergés, Joan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the field of virtual higher education at the University of Vigo (UVigo, Spain) there is a massive videoconference service, integrated into the Remote Campus, which can be used for virtual teaching; and, optionally, also for the automatic recording of these classes in videos. The appearance of new technologies such as deepfake and face-to-face translation will allow, in addition to the translation/dubbing of the audio in these video classes, the manipulation of the image so that the change of language is not noticed when speaking; so that lip synchronization is also done automatically.